Methods and Varieties of Guidance According to Imām Māturīdī - Harun Çağlayan (ULUM, 2019)
Māturīdī, one of the prominent Kalām scholar, is mostly considered to have played a significant role in the construction of a sustainable religious approach today. This recognition originates from his joint reference to intellect and divine inspiration with regard to issues in Kalām in addition to his contributions to the Sunni way of thinking. His balanced use of the intellect and divine inspiration in his solutions for issues of Hidāyat increased his popularity. In the Muslim world, just as in any other community, perception of reality or guidance not as a process but as outright values of their community causes such problems as religious fanaticism and advocacy for sole truth. To solve such problems, a sound understanding of guidance in Muslim communities should be constructed in the light of scientific and social realities. In this respect, determining unique and comprehensive interpretations of Māturīdī of the issue will be of great help for establishing a peaceful religious understanding for the common future of humanity. In the center of Māturīdī’s interpretations of guidance lies his approach to guidance with respect to its methods and varieties. Besides presenting the definitions of these methods and varieties, the current study analyzes Māturīdī’s interpretations of how these methods and varieties interact.